Comparing Places of Worship as Tourist Destinations Based on Architectural Attraction: An Analysis on the West Indonesian Protestant Church (GPIB) Marga Mulyo, Yogyakarta - Revta Fariszy; Yuseptia Angretnowati; Keny Rahmawati; Meike Lusye Karolus; Sauptika Kancana (Centre of Excellence in Tourism Udayana University, 2025)
Religious‑heritage tourism in Indonesia has predominantly highlighted temples and mosques, leaving Protestant heritage sites such as the Western Indonesian Protestant Church (GPIB) Marga Mulya underrepresented in both scholarship and tourism promotion. This study aims to assess and compare the tourism potential of GPIB Marga Mulya, the oldest Protestant church in Yogyakarta, with other architecturally significant places of worship in Indonesia, to inform sustainable heritage‑tourism strategies. Using a comparative qualitative descriptive approach, the research applies SWOT analysis, supported by literature review, field observation, and interviews with church stakeholders, to evaluate historical value, architectural features, accessibility, and visitor engagement. Findings show that while GPIB Marga Mulya benefits from a central Malioboro location and rich Dutch colonial heritage, it is constrained by limited promotion, inadequate visitor facilities, and diminished visual prominence. In contrast, sites such as Cut Meutia Mosque in Jakarta and Santo Petrus Cathedral in Bandung leverage active programming, segmented community outreach, and event‑based attractions to strengthen their tourism appeal. This study contributes to expanding the scope of religious‑heritage tourism research to include Protestant sites and offers practical recommendations for positioning strategies, though its conclusions are limited to five case studies within the Indonesian context.